The association of thyroid stimulating hormone levels and intrauterine insemination outcomes of euthyroid unexplained subfertile couples. (September 2019) - Turgay, Batuhan; Şükür, Yavuz Emre; Ulubaşoğlu, Hasan; Sönmezer, Murat; Berker, Bülent; Atabekoğlu, Cem; Aytaç, Ruşen; Özmen, Batuhan
Abstract: Objective: To investigate the effect of different TSH (0.5–2.49 mIU/L and 2.5–4.5 mIU/L) levels on intrauterine insemination (IUI) outcomes of euthyroid unexplained subfertile patients who are negative for thyroid antibodies. Study design: In this retrospective cohort study, data of euthyroid subfertile patients who underwent IUI due to unexplained infertility at a university-based infertility clinic between January 2013 and December 2014 were reviewed. A total of 156 patients of them were categorized into two groups according to pre-conceptional TSH levels. The first study group consisted of patients with serum TSH levels 0.5–2.49 mIU/L and the second study group consisted of patients with serum TSH levels 2.5–4.5 mIU/L. The primary outcome measure was live birth rate. Results: Demographics and cycle characteristics of the study groups were similar. There were no statistically significant differences between the study groups regarding main outcome measures (live birth rate, P = 0.82; clinical pregnancy rate, P = 0.64; miscarriage rate, P = 0.57). Conclusion: Pre-conceptional TSH levels ranging between 0.5–4.5 mU/L does not appear to have a significant effect on IUI outcome of euthyroid women who are negative for thyroid antibodies.